2014
DOI: 10.2147/rmhp.s64585
|View full text |Cite
|
Sign up to set email alerts
|

Association of positive fluid balance and cardiovascular complications after thoracotomy for noncancer lesions

Abstract: ObjectiveThe purpose of this study was to explore the influence of positive fluid balance on cardiovascular complications after thoracotomy for noncancer lesions.MethodsAfter approval from an institutional review board, a retrospective cohort study was conducted. All consecutive patients undergoing thoracotomy between January 1, 2005 and December 31, 2011 in a single medical center were recruited. The primary outcome of the study was the incidence of cardiovascular complications, which were defined as cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The strength of this study is the demonstration that the fluid accumulation threshold is based on the individual patient’s body size instead of being a fixed amount of fluid. 7 , 27 This study also verified the lower cutoff threshold, as compared with previous studies, that impacts surgical ICU outcomes. 6 , 12 However, our study had some limitations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The strength of this study is the demonstration that the fluid accumulation threshold is based on the individual patient’s body size instead of being a fixed amount of fluid. 7 , 27 This study also verified the lower cutoff threshold, as compared with previous studies, that impacts surgical ICU outcomes. 6 , 12 However, our study had some limitations.…”
Section: Discussionsupporting
confidence: 84%
“… 6 However, recent evidence found that a positive fluid balance of more than 2,000 mL (approximately 4%–7% of dry weight) during the intraoperative period was a strong risk factor for cardiovascular complications in thoracic surgical patients. 7 Nonetheless, to date, there has been little evidence to demonstrate the threshold for concern and influence of fluid accumulation on outcomes, especially in high risk and critically ill surgical patients. 6 In addition, accurate fluid output was difficult to measure in some surgical patients because of multiple drains, wounds, and insensible loss.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Pipanmekaporn et al 16 reported an incidence of 6.7% (48 patients) for cardiovascular complications in a study of 720 patients undergoing thoracotomy for indications other than cancer. The rate of cardiovascular complications was 22.2% in patients with a positive fluid balance of >2,000 mL and 7.0% in patients with a fluid balance of ≤2,000 mL ( p =0.005).…”
Section: Discussionmentioning
confidence: 99%